Students Perceptions and Experiences of Intercultural Communication in Library and Information Science Education Programmes - Virkus, Sirje; Uukkivi, Anne (Qualitative and Quantitative Methods in Libraries, 2017)
This paper discusses the research project that explored intercultural communication in library and information science education, more specifically in online learning environment. This research focuses on answering the following central question: What is the nature of successful intercultural communication and what are the factors and conditions which support this? Findings of this research project were used to develop a framework which identified a series of factors that needs to be considered in the process of facilitating intercultural communication in library and information science education.